(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
Mqamat Hariri and Naftha al-Masdour Nasavi, as two prose works in the ancient Arabic and Persian literature, have a special technical prose and stylistic aspects with the spokespersons, so that up to now there has not been a joint research between the two authors but separately many researches have been done on the writing, rhetorical and aesthetic aspects of Nafteh al-Masdour and the exquisite coordinates and more volitional The stylistic coordinates of the two works have a comparative and analytical aspect, the results of both of them have been used to a good extent in terms of writing assignments, tendency to poetry and use of language abilities.; it is true that the subject of their story is different, but in terms of his technical prose, he is very close. In this paper, Hariri authorities and Fatha al-Masdour Nasavi studied the structure of a technical style and attempted to clarify the role of the "style" element in it in order to create a link between other textual elements.